Possibilities of qualitative modeling in bankruptcy predictions - Krejčíř, Jaroslav; Rašková, Hana; Dohnal, Mirko (Univerzita Pardubice, 2011)
The issue of bankruptcy has long been paid a considerable interest at practical and theoretical levels using more sophisticated tools such as genetic algorithms, neural networks, statistical methods etc. This article describes application of less a used method of Qualitative models which can forecast changes in trends and thus contribute to solving the selected problem even without entirely accurate knowledge of the quantitative data. The model is based on three qualitative values only: increasing, constant, decreasing used to describe the corresponding trends. The result presents eleven possible scenarios and sixteen transitions among them.
Keywords: bankruptcy; prediction; qualitative modeling; scenario